Acceptability, effectiveness and safety of a Renew® anal insert in patients who have undergone restorative proctocolectomy with ileal pouch–anal anastomosis. (8th October 2018) - Segal, J. P.; Leo, C. A.; Hodgkinson, J. D.; Cavazzoni, E.; Bradshaw, E.; Lung, P. F. C.; Ilangovan, R.; Vaizey, C. J.; Faiz, O. D.; Hart, A. L.; Clark, S. K.
Abstract: Introduction: Restorative proctocolectomy has gained acceptance in the surgical management of medically refractive ulcerative colitis and cancer prevention in familial adenomatous polyposis. Incontinence following restorative proctocolectomy occurs in up to 25% of patients overnight. The Renew ® insert is an inert single‐use device which acts as an anal plug. The aim of this study was to assess the acceptability, effectiveness and safety of the Renew ® insert in patients who have undergone restorative proctocolectomy. The device has yet to be assessed in patients who have undergone restorative proctocolectomy. Method: This was a prospective study exploring the acceptability, effectiveness and safety of the Renew ® insert in improving incontinence in patients who had undergone restorative proctocolectomy. A total of 15 patients with incontinence were asked to use the Renew ® insert for 14 days following their standard care. The Incontinence Questionnaire–Bowels was used pre‐ and posttreatment to assess response and patients were asked to report the perceived acceptability, effectiveness and safety of the device at the end of the trial. Results: The device was acceptable to 8/15 (53%) of patients and was effective in 6/15 (40%). Only 2/15 (13%) of patients raised any safety concerns, and these were minor. The device was associated with a significant reduction in night seepage ( P  = 0.034). Conclusion: In a small study, the Renew ® insert can be both acceptable and effective and is also associated with few safety concerns. It is also associated with significant reductions in night‐time seepage.